Analisis Disiplin Kerja Pegawai Pada Badan Riset Dan Inovasi Daerah Provinsi Jambi - Eka Wahyu Permadi; Zulfina Andriani; Try Syeftiani (Journal of Islamic Banking, 2025)
This study aims to analyze the implementation of employee work discipline at the Regional Research and Innovation Agency (BRIDA) of Jambi Province. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation with informants consisting of leaders and employees of BRIDA Jambi Province. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, as well as data validity testing using source triangulation. The results of the study indicate that employee work discipline at BRIDA Jambi Province is quite good, but not yet fully optimal. This is evident from several indicators of work discipline, namely attendance, compliance with work regulations, compliance with work standards, level of alertness, and work ethics. There are still employees who arrive late, leave after work hours, and do not comply with established regulations and procedures. However, some employees have demonstrated a fairly good work ethic and responsibility in carrying out their duties. Therefore, it is necessary to strengthen inherent supervision (WASKAT), firm leadership, and continuous coaching to improve employee work discipline at BRIDA Jambi Province